High Resolution Proteomic Analysis of Subcellular Fractionated Boar Spermatozoa Provides Comprehensive Insights Into Perinuclear Theca-Residing Proteins - Zhang, Min; Chiozzi, Riccardo Zenezini; Skerrett-Byrne, David A.; Veenendaal, Tineke; Klumperman, Judith; Heck, Albert J. R.; Nixon, Brett; Helms, J. Bernd; Gadella, Bart M.; Bromfield, Elizabeth G. (Frontiers in Cell and Developmental Biology, 2022)
The perinuclear theca (PT) is a highly condensed, largely insoluble protein structure that surrounds the nucleus of eutherian spermatozoa. Recent reports have indicated that the PT unexpectedly houses several somatic proteins, such as core histones, which may be important post-fertilization during re-modelling of the male pronucleus, yet little is known regarding the overall proteomic composition of the PT. Here, we report the first in depth, label-free proteomic characterization of the PT of boar spermatozoa following the implementation of a long-established subcellular fractionation protocol designed to increase the detection of low abundance proteins. A total of 1,802 proteins were identified, a result that represents unparalleled depth of coverage for the boar sperm proteome and exceeds the entire annotated proteome of the Sus scrofa species so far. In the PT structure itself, we identified 813 proteins and confirmed the presence of previously characterized PT proteins including the core histones H2A, H2B, H3 and H4, as well as Ras-related protein Rab-2A (RAB2A) and Rab-2B (RAB2B) amongst other RAB proteins. In addition to these previously characterized PT proteins, our data revealed that the PT is replete in proteins critical for sperm-egg fusion and egg activation, including: Izumo family members 1–4 (IZUMO1-4) and phosphoinositide specific phospholipase ζ (PLCZ1). Through Ingenuity Pathway Analysis, we found surprising enrichment of endoplasmic reticulum (ER) proteins and the ER-stress response in the PT. This is particularly intriguing as it is currently held that the ER structure is lost during testicular sperm maturation. Using the String and Cytoscape tools to visualize protein-protein interactions revealed an intricate network of PT protein complexes, including numerous proteasome subunits. Collectively, these data suggest that the PT may be a unique site of cellular homeostasis that houses an abundance of protein degradation machinery. This fits with previous observations that the PT structure dissociates first within the oocyte post-fertilization. It remains to be explored whether proteasome subunits within the PT actively assist in the protein degradation of paternal cell structures post-fertilization and how aberrations in PT protein content may delay embryonic development.